2022
DOI: 10.1038/s41598-022-10679-x
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal breast milk microbiota and immune markers in relation to subsequent development of celiac disease in offspring

Abstract: The potential impact of the composition of maternal breast milk is poorly known in children who develop celiac disease (CD). The aim of our study was to compare the microbiota composition and the concentrations of immune markers in breast milk from mothers whose offspring carried the genetic predisposition to CD, and whether they did or did not develop CD during follow-up for the first 3 years of life. Maternal breast milk samples [CD children (n = 6) and healthy children (n = 18)] were collected 3 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Tominaga et al (2021b) found increased levels of Corynebacterium (p<0.01), Peptoniphilus (p<0.05), Anaerococcus (p<0.05) and Porphyromonas (p<0.01). These genera have been associated with haematogenous or tissue infections when translocated or overgrown (Brown et al, 2014; Tidjani Alou et al, 2016; Sędzikowska and Szablewski, 2021; Štšepetova et al, 2022). However, their role in intestinal inflammation is less clear at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…Tominaga et al (2021b) found increased levels of Corynebacterium (p<0.01), Peptoniphilus (p<0.05), Anaerococcus (p<0.05) and Porphyromonas (p<0.01). These genera have been associated with haematogenous or tissue infections when translocated or overgrown (Brown et al, 2014; Tidjani Alou et al, 2016; Sędzikowska and Szablewski, 2021; Štšepetova et al, 2022). However, their role in intestinal inflammation is less clear at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…Since a 2023 systematic review, seven newly identified articles were considered relevant, and full papers were retrieved. [4][5][6][7][8][9][10][11][12][13] Among these, the only study contributing new data was a retrospective case-control study from Iran. 10 This study compared 186 children diagnosed with CD (mean age: 4.8 years) from a single centre with 186 non-CD controls (mean age: 4.1 years).…”
Section: Q6 Gluten Intake By the Mother During Pregnancy And Lactationmentioning
confidence: 99%
“…Since a 2023 systematic review, seven newly identified articles were considered relevant, and full papers were retrieved 4‐13 . Among these, the only study contributing new data was a retrospective case‐control study from Iran 10 .…”
Section: Statements and Recommendationsmentioning
confidence: 99%
“…Celiac disease (CeD) is an autoimmune disorder triggered by gluten and related prolamins that occurs in genetically predisposed individuals [ 118 ]. Genetic susceptibility and gluten ingestion do not have the capacity of inducing the disease alone, suggesting that several additional factors might interfere with disease pathogenesis [ 119 , 120 , 121 ]. Intestinal dysbiosis in CeD has been the subject of different studies as the major environmental factor involved in CeD underlying mechanisms.…”
Section: Microbiota and The Digestive Pathologymentioning
confidence: 99%